Special dietary needs: Contributions of continuing education for teachers in the early years of elementary school (Revista Contexto & Educação, 2026)
This research is an excerpt from the dissertation of one of the authors, which aimed to analyze the contributions of a continuing education proposal for teachers of the Early Years of Elementary School on the theme of Special Dietary Needs. The research methodology was collaborative with a qualitative approach. The training was carried out in the form, in which 12 teachers participated, of a workshop and the approach consisted of moments of discussion of the theoretical content on the subject and a culinary practice with inclusive recipes. The data were produced from video recordings of the activities, conversation circles and questionnaire, later analyzed according to Discursive Textual Analysis. The results indicated that the proposal provided a space for dialogue, questions and awareness about the inclusion of people with dietary restrictions, promoting and expanding knowledge on the subject, since some teachers experienced these issues. Enabling reflections and possibilities for actions to make the school and social environment more inclusive.
Keywords: Teacher formation; Inclusive Food; Science teaching; Special Dietary Needs